2009
DOI: 10.1109/tmag.2009.2025390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Nanoparticle Additive on Characteristics of Magnetorheological Fluid

Abstract: Magnetorheological (MR) fluids, suspension of magnetic pure carbonyl iron (CI) in non magnetic carrier, were prepared with and without magnetic CI nanoparticle additive in this study. Initially, the magnetic CI nanoparticle additive was synthesized in a rather simple process of decomposition of penta carbonyl iron (Fe(CO) 5 ) using oleyl amine and kerosene. Magnetic property and morphology of the synthesized magnetic CI nanoparticles were confirmed via vibration sample magnetometer (VSM) and transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…It has been demonstrated from these works that MRGs can produce very high yield stress without any sedimentation behaviour. In addition, it has been shown that the field-dependent rheological properties of MRGs can be enhanced by adding certain additives, such as nanosized carbon [31]. Besides works on the field-dependent properties, the controllability of the initial viscosity of MRGs by addition of small amounts (5 wt%) of kerosene has been examined [32].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated from these works that MRGs can produce very high yield stress without any sedimentation behaviour. In addition, it has been shown that the field-dependent rheological properties of MRGs can be enhanced by adding certain additives, such as nanosized carbon [31]. Besides works on the field-dependent properties, the controllability of the initial viscosity of MRGs by addition of small amounts (5 wt%) of kerosene has been examined [32].…”
Section: Introductionmentioning
confidence: 99%
“…21 The shear stress increases with the higher magnetic field strength as a typical feature of the MR fluid with the formation of robust chain structure. 22 The GO/CI mixture fluid shows similar, even a little higher, shear stress at the same magnetic field compared with CI fluid which may be due to the magnetic response of GO additives. 23 We can, however, make sure that the addition of GO did not affect the MR properties of CI particles.…”
Section: E724-2mentioning
confidence: 88%
“…To increase the stability of MRF also the following thixotropic agents can be added to the MR suspension (de Vicente et al, 2003; Kang et al, 2015): ferrous oleate, lithium stearate, Aerosil 200, Arsil 1 100 (Xu et al, 2018), ferrous naphthalate or ferrous oleate, fumed silica (Aruna et al, 2021), wormlike surfactant micelles (Wu et al, 2006), polystyrene (Dorosti et al, 2020; Kumbhar and Patil, 2014; Quan et al, 2014), microcrystalline cellulose (Chuah et al, 2015), nanowires (Pu and Jiang, 2005), silica nanoparticles (Bae et al, 2017) fullerene powder, carbon nanotubes, graphene nanoplatelets, and others (Cvek et al, 2018). Another way to enhance MRFs stability is applied as a media poly(vinyl pyrrolidone) and carbon nanotubes (Ngatu et al, 2008), ionic liquids (Pu and Jiang, 2005) compounds like aluminum stearate (López-López et al, 2005) tetramethylammonium hydroxide (Fonseca et al, 2016), soy lecithin (Kolekar et al, 2019), N-glucose ethylenediamine triacetic acid (GED3A) stearate and oleate (Chin et al, 2001; Kolekar et al, 2019), emulsifiers like Tween-60, Span-60, OP emulsifier, Tween-80, and Span-80 (Zhang et al, 2009), n-tetradecyltri-ethoxysilane, diethyl-n-octyl-, and n-tetradecylphos-phonates (Belyavskii et al, 2006), oleylamine (Fei et al, 2020; Lu et al, 2016; Song et al, 2009), hydrophilic carbon shell (Lu et al, 2016).…”
Section: Stabilization and Tribological Propertiesmentioning
confidence: 99%